Code-Switching among Healthcare Workers and Patient Comprehension in Ughelli Central Hospital, Delta State (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study looks at the part code-switching plays in healthcare communication at Ughelli Central Hospital, Delta State. Code-switching is a regular occurrence in healthcare environments given Nigeria's multilingual environment, when many local languages are spoken alongside English. The paper investigates the elements affecting code-switching, its supposed advantages, and the possible difficulties it causes to provide efficient healthcare. The study involved a sample of 255 respondents including patients and healthcare professionals. Structured questionnaires were used to gather data; Likert scale and percentage analysis was then applied in analysis. The results show that code-switching improves communication by making medical consultations more relevant, particularly in cases of healthcare professionals switching to local languages, therefore raising patient comfort and understanding. Excessive code-switching, particularly in individuals less adept in the languages being utilized, also generated questions regarding possible confusion. Although code-switching was proven to be very helpful for bilingual or multilingual patients, if not done sensibly it may cause discomfort for others. The study emphasizes the need of striking a balance between language use in medical environments to guarantee good communication, boost patient confidence, and prevent misinterpretation. Advice calls for bilingualism, training healthcare professionals in language competency and communication techniques, and creation of multilingual materials to increase patient understanding and satisfaction.